Naturens unatur - Norup, Lis (Passage - Tidsskrift for litteratur og kritik, 2026)
The Unnaturalness of Nature The article examines the part of the French author J.-K. Huysmans’ oeuvre that deals with the devastated, polluted, and neglected nature. The first example analyzes his description of the natural environment in the peripheral zones outside Paris – unproductive, unused, and indeterminate areas, the so-called terrains vagues. The second example focuses on La Bièvre, Paris’s second river, whose heavily contaminated waters were gradually being canalized in the decades around the turn of the last century. Together, these two examples illustrate Huysmans’ distinctive descriptive style.